Improving Thematic Learning Outcomes Using Problem Based Learning Models in Class III SD - Rohayati, Rohayati (Universitas Sebelas Maret, 2020)
This study aims to improve thematic learning outcomes by using the Problem Based Learning (PBL) model in class III SD Negeri Ketangan 02. In this study applying the type of classroom action research (CAR) using qualitative and quantitative approaches. The research subjects were third grade students of SD Negeri Ketangan 02 semester 2 for the 2019/2020 academic year with a total of 16 students. This research was conducted in two cycles. The results of the first cycle research on RPP an average of 81,48% (B), increased in the second cycle to 92.59% (SB), the implementation of the first cycle on teacher activities an average of 82.50% (B) increased in the second cycle to 95.00% (SB), the implementation of the first cycle on student activity an average of 82.50% (B) increased in the second cycle to 95.00% (SB). Student learning outcomes in the first cycle averaged 78 (C), increased in the second cycle to 93 (SB). So it can be concluded that learning by applying the Problem Based Learning model is able to improve student learning outcomes in class III teamtic learning at SD Negeri Ketangan 02.